DENGOSA: Um Sistema de Informação Geográfica para Apoio à Decisão no Controle de Epidemias - Bezerra, Arthur; Bento Filho, João José; Braga, Reinaldo; Oliveira, Carina; Oliveira, Mauro (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
Nowadays, epidemiological surveillance is the main challenge in the Brazilian public health system due to the problem to maintain information in real time about diseases. In this context, dengue, zica and chikungunya are increasing disease and the number of cases in different regions is not updated in real time neither presented in an easy way. Consequently, the Brazilian government has the constant challenge to efficiently distribute public health resources in the locations for the high number of dengue cases. Therefore, this paper presents DENGOSA, a low cost web system that analyzes the number of dengue cases by region as well as presents epidemic regions in maps. Finally, DENGOSA provides interoperabilty services for the systems communication and optimizes the decision-making process for the managers of public health system. Besides that, it is flexible to provide services to notify the population about epidemic regions.